Relationship of the “Dequada” Phenomenon with Mercury Methylation in Pantanal, Brazil - Nunes, Glaucia A.; Ramos, Dayana D.; Forti, Juliane C. [UNESP]; Ramos, Diovany D.; Oliveira, Lincoln C. S.; Junior, David S. S. [UNESP]; Santo, Gabriel E. [UNESP]; Santos, Felipe A. [UNESP] (MDPI, 2024)
The illegal activity of gold mining in the Brazilian Pantanal is contaminating the aquatic ecosystem with mercury. This contamination has been potentiated by mercury methylation due to a typical natural phenomenon of the Pantanal ecosystem known as “dequada”. The present study estimated in the laboratory the temporal production of methylmercury at two timepoints: the beginning of a flood, when the “dequada” phenomenon occurs, and the dry season without such phenomenon. After collecting water and sediment, experiments were performed with microcosms to reproduce conditions close to nature. To monitor the concentration of methylmercury, 1.0 mg L−1 of Hg2+ was added to water and sediment experiments in the Castelo and Saracura bays, both during the “dequada” and without it; monitoring lasted for 25 days. The methylmercury concentration was analyzed using atomic fluorescence spectrometry, total organic carbon using TOC 5000A, and physical and chemical parameters such as pH, redox potential, and dissolved oxygen with a multi-parameter probe. The results led to the conclusion that the “dequada” phenomenon significantly affected mercury methylation, because the environmental changes caused by this phenomenon such as the increased concentration of organic matter, decreased dissolved oxygen, and decreased pH, potentiated mercury methylation. During the “dequada” in the Castelo bay, the methylation rate was 3.5 times higher (6297.56 ng L−1) than in the experiment without the “dequada” (1827.44 ng L−1). Therefore, the gold mining activity in Pantanal can cause great damage to the ecosystem because this environment favors mercury methylation, making its most toxic form active in the aquatic ecosystem of Pantanal.
Keywords: dequada phenomenon; methylmercury; Pantanal; water contamination